2017
DOI: 10.6063/motricidade.10049
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of exhausting exercise and overtraining on the immune response: Th1 and Th2 profile

Abstract: Although physical inactivity figures as one of the main causes attributed to mortality, the damage caused by excessive exercise is also a reality. Professional athletes, amateur or uncompetitive modalities beneficiaries are often affected by deleterious conditions resulting from excessive exercise, such as neurological, endocrine and immune origin. The thin line between losses and benefits of successive fatiguing sessions effort depends on the understanding of concepts and methodological training principles. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
1
19
0
2
Order By: Relevance
“…Malnutrition, nutritional deprivation, and low-energy availability are thought to be one of the major causes of immunodeficiency where the most common immune defects are atrophy of lymphoid tissues (e.g., thymus), reduced maturation of T-lymphocytes, an imbalance in the ratio of CD4/CD8 T-lymphocytes, and predominant T H 2 helper cell response (5459), alterations that were consequently also suggested by the leukocyte transcriptome in our study (Figures 3, 5). These immune system defects have been previously reported to be mediated by reduced levels of leptin caused by low-energy availability and exhaustive exercise (12, 60)—a response also observed in the diet group participants of our study after the weight loss period ( PRE-MID ). On the other hand, leptin administration and moderate levels of exercise have successfully prevented these immune system alterations and consequent immunosuppression (55).…”
Section: Discussionsupporting
confidence: 82%
“…Malnutrition, nutritional deprivation, and low-energy availability are thought to be one of the major causes of immunodeficiency where the most common immune defects are atrophy of lymphoid tissues (e.g., thymus), reduced maturation of T-lymphocytes, an imbalance in the ratio of CD4/CD8 T-lymphocytes, and predominant T H 2 helper cell response (5459), alterations that were consequently also suggested by the leukocyte transcriptome in our study (Figures 3, 5). These immune system defects have been previously reported to be mediated by reduced levels of leptin caused by low-energy availability and exhaustive exercise (12, 60)—a response also observed in the diet group participants of our study after the weight loss period ( PRE-MID ). On the other hand, leptin administration and moderate levels of exercise have successfully prevented these immune system alterations and consequent immunosuppression (55).…”
Section: Discussionsupporting
confidence: 82%
“…During the exercise recovery, a secondary lymphopenia appears. This seems to be due to a decrease in Th lymphocyte counts through a redistribution of the cells into the non-lymphoid and lymphoid organs (Krüger et al, 2008;Guimarães et al, 2017). In addition, apoptosis also seems to occur unevenly between highly differentiated T cells (Krüger et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…One of the various arguments to encourage moderate and periodic exercise refers to the protection of cells against infections caused by intracellular microorganisms (e.g., viruses), based on the balance between cellular and humoral immune responses, with discreet readiness for the Th1 profile. [17][18][19] For example, data from our group revealed that lymph node cells and mouse macrophage supernatants, after 10 to 12 weeks of moderate exercise, expressed more pro-inflammatory cytokines (e.g., IFN-γ and TNF), while the concentration of anti-inflammatory cytokines (e.g., IL-4 and IL-10) decreased significantly compared to the physically inactive group. 17,18,30 The reduction of the post-intervention IL-10/IFN-γ ratio converged with the hypothesis of the predisposition of the protective cell profile (Th1) with moderate exercise.…”
Section: Basic Considerations About Immune Response and Physical Exermentioning
confidence: 83%
“…17,18,30 The reduction of the post-intervention IL-10/IFN-γ ratio converged with the hypothesis of the predisposition of the protective cell profile (Th1) with moderate exercise. 15,[17][18][19]30 Furthermore, macrophages of mice infected with the protozoa Leishmania major produced more IL-12 and NO compared to macrophages in the sedentary control group. 17,18 We should also take note of the greater microbicidal activity of these cells and the reduction infection rates and the number of parasites isolated from the paw of infected animals.…”
Section: Basic Considerations About Immune Response and Physical Exermentioning
confidence: 98%
See 1 more Smart Citation